Continuous Unilateral Erector Spinae Plane Block versus Intravenous Analgesia in Minimally Invasive Cardiac Surgery: A Randomized Controlled Trial - Hoan, Duong Thi; Hung, Duong Duc; Dat, Pham Quoc; Tu, Nguyen Huu (Open Access Macedonian Journal of Medical Sciences, 2022)
Objectives: the study was conducted to assess the safety and efficacy of anesthesia under the erector spinae plane block (ESPB) in minimally invasive cardiac surgery (MICS). Methods: a prospective, randomized controlled trial was carried out in 56 adult patients who underwent MICS via a right thoracic incision at Vietnam National Heart Institute, Bach Mai hospital, Vietnam. Patients were randomly allocated into two groups: ESPB and conventional analgesia (intravenousmorphine patient-controlled analgesia, PCA). Patients in ESPB group received ultrasound-guided unilateral ESPB at the T4/T5 transverse process level, and the tip of the catheter was advanced 5cm beyond the tip of the needle; injected with 20 ml ropivacaine 0.5%. At the cardiac ICU, patients received paracetamol (1g every 6 hours), continuous infusion ropivacaine 0.1% 0.2ml/kg/hour. Patients in the PCA group received paracetamol (1g every 6 hours) and intravenous morphine PCA. All patients were followed for 72 hours after being extubated. Results: the resting VAS score was significantly lower in ESPB group at the time H4, H8, H12, H16, H36, H42, H48, H54, H60, H66 after extubated compared to that of the PCA group (p< 0.05). The dynamic VAS score at was also significantly lower in the ESPB group at all measured time points (p<0.05). Only 4 patients in the ESPB group required intravenous morphine PCA with the mean amount morphine were statistically lower in the ESPB group compared to the PCA group at 24 hours, 48 ​​hours, 72 hours postoperative. No serious adverse events such as neurological complications, bleeding or infection were observed in both groups. Conclusion: ESPB is an effective analgesic for MICS via thoracic incision in reducing the VAS score and the morphine required. It is also a safe method with no severe ESPB-related complications.